Cd2+ and Pb2+ complexation by glutathione and the phytochelatins. (1st April 2017) - Jacquart, Aurélie; Brayner, Roberta; El Hage Chahine, Jean-Michel; Ha-Duong, Nguyet-Thanh
Abstract: Phytochelatins or PCn, (γGlu-Cys)n -Gly, and their glutathione (GSH) precursor are thiol-rich peptides that play an important role in heavy metal detoxification in plants and microorganisms. Complex formation between Cd 2+ and Pb 2+ and GSH or PCn (n = 2, 4 and 6) are investigated by microcalorimetry, absorption spectrophotometry and T-jump kinetics. Complex formation with Pb 2+ or Cd 2+ is exothermic, and induces ligand metal charge transfer bands in UV absorption spectral range, which implies the formation of a coordination bond between the metal and the thiol groups of the phytochelatins. Absorption spectra and microcalorimetry experiments allow the determination of the affinity constants and the stoichiometry of the complexes. We show that the three PCn interact with Pb 2+ to form the 1:1 and 2:1 M:L complexes, with similar affinity constants (log K 11 Pb ∼4.6, log K 21 Pb ∼11.4). These affinities are independent of the number of thiols and are, moreover, lower than those determined for complex formation with Cd 2+ . On the other hand, with Cd 2+, PC2-Cd, PC2-Cd2, (PC2)3 -Cd2, PC4-Cd, PC4-Cd2, PC6-Cd, (PC6)2 -Cd3 and PC6-Cd3 complexes are detected. Furthermore, for PC4-Cd, the 1:1 complex is the most stable: affinity constant (log K 11 Cd ∼7.5). Kinetic studies indicate that complex formation between Cd 2+ and GSH occurs in the ms range; direct rate constant k obs  = (6.8 ± 0.3) 10 6  M −1  s −1 and reverse rate constant k − obs  = 340 ± 210 s −1 . Thus, when encapsulated in a silica matrix, PCn can be good candidates for heavy metal detection. Highlights: Cd uptake by glutathione occurs in the ms range. The complexation of Cd by phytochelatins is exothermic process. Phytochelatins are good candidates for heavy metals sensors.